Heat stress in temperate and tropical maize hybrids: Kernel growth, water relations and assimilate availability for grain filling - Rattalino Edreira, Juan Ignacio (2014)
Several studies have indicated that maize (Zea mays L.) kernel weight is severely affected by heat stress, but this response was never evaluated under field conditions. Our objective was to assess the effect of brief episodes of above-optimum temperatures on the dynamics of biomass and water accumulation in kernels of maize hybrids with contrasting tolerance to heat stress. Heat effect on assimilate supply from the plant (i.e., current biomass production and water-soluble carbohydrates in stem) to developing grains was also analyzed. Field experiments included a factorial combination of (i) three hybrids (Te: temperate; Tr: tropical; TeTr: Te×Tr), (ii) two temperature regimes, control and heated during daytime hours (ca. 33?40 °C at ear level), and (ii) three 15-d periods (GS1: immediately before anthesis; GS2: from silking onwards; GS3: early phase of active grain filling). Heat effects on final kernel weight were larger (i) when they occurred during the first half of effective grain ﬁlling (-23.1% for GS3) than around ﬂowering (-4.8% for GS1, -6.3% for GS2), and (ii) for the Te hybrid (-20.4%) than for the TeTr (-8.6%) and the Tr (-6.8%) hybrids. Heating around flowering (i) enhanced the assimilate availability per kernel during the effective grain-filling period, (ii) increased carbohydrates reserves in stem at physiological maturity, (iii) and had no significant effect on the dynamics of biomass and water accumulation in kernels. The opposite trend was detected among plots heated during GS3, which mostly exhibited the interruption of grain filling. Robust associations were established between (i) carbohydrate reserves in stem at physiological maturity and assimilate availability per kernel during effective grain filling (r²=0.49; P <0.001), and (ii) the rate of water loss from kernels and the duration of effective grain filling (r²=0.71; P<0.001). These responses underlay the enhanced sensitivity to heat stress of the hybrid with full temperate genetic background.